ERK1/2-mediated activation of DRP1 regulates mitochondrial dynamics and apoptosis in chondrocytes. Issue 2 (February 2022) - Ansari, M.Y.; Novak, K.; Haqqi, T.M.
Summary: Objective: To determine the Dynamin-related protein 1 (DRP1) regulation of mitochondrial fission in chondrocytes under pathological conditions, an area which is underexplored in osteoarthritis pathogenesis. Design: DRP1 protein expression was determined by immunohistochemistry (IHC) or immunofluorescence (IF) staining of cartilage sections. IL-1β-induced DRP1 mRNA expression in chondrocytes was quantified by qPCR and protein expression by immunoblotting. Mitochondrial fragmentation in chondrocytes was visualized by MitoTracker staining or IF staining of mitochondrial marker proteins or by transient expression of mitoDsRed. Mitochondrial reactive oxygen species (ROS) levels were determined by MitoSOX staining. Apoptosis was determined by lactate dehydrogenase (LDH) release assay, Caspase 3/7 activity assay, propidium iodide (PI), and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining and IF staining of cleaved caspase 3. Cytochrome c release was determined by confocal microscopy. Surgical destabilization of the medial meniscus (DMM) was used to induce osteoarthritis (OA) in mice. Results: Expression of DRP1 and mitochondrial damage was high in human OA cartilage and in the joints of mice subjected to DMM surgery which also showed increased chondrocytes apoptosis. IL-1β-induced mitochondrial network fragmentation and chondrocyte apoptosis via modulation of DRP1 expression and activity and induce apoptosis via Bax-mediated release of Cytochrome c. Pharmacological inhibition of DRP1 activity by Mdivi-1 blocked IL-1β-induced mitochondrial damage and apoptosis in chondrocytes. Additionally, IL-1β-induced activation of extracellular signal-regulated kinase 1/2 (ERK1/2) is crucial for DRP1 activation and induction of mitochondrial network fragmentation in chondrocytes as these were blocked by inhibiting ERK1/2 activation. Conclusions: These findings demonstrate that ERK1/2 is a critical player in DRP1-mediated induction of mitochondrial fission and apoptosis in IL-1β-stimulated chondrocytes.